The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00266-015-0512-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Extended Lateral Upper Arm Free Flap for Tongue Reconstruction After Radical Glossectomy for Tongue Cancer

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Debate about differences in functional outcomes of these 2 flaps is extensive, with most authors concluding that both have similar results and tending to favor the latter because of suggested better resistance to postradiotherapy deformity, donor site potential complications, and aesthetic concerns . Many other free flap options have been described for reconstruction of the partial glossectomy defect, including the lateral arm, gracilis, vertical rectus abdominis myocutaneous, tensor fasciae latae, peroneal artery, medial sural perforator, anteromedial, anterior tibial perforator, superficial circumflex iliac artery, deep inferior epigastric artery perforator, and supraclavicular and rectus abdominis musculoperitoneal flaps. Most of those flaps have shown good outcomes at the expense of a difficult dissection, donor site morbidity, inconvenience of flap harvest, or the need of more extensive (and expensive) preoperative evaluation, therefore, they are reserved as the second choice for comorbid patients or those in which traditional ALT or radial forearm could not be used for other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Debate about differences in functional outcomes of these 2 flaps is extensive, with most authors concluding that both have similar results and tending to favor the latter because of suggested better resistance to postradiotherapy deformity, donor site potential complications, and aesthetic concerns . Many other free flap options have been described for reconstruction of the partial glossectomy defect, including the lateral arm, gracilis, vertical rectus abdominis myocutaneous, tensor fasciae latae, peroneal artery, medial sural perforator, anteromedial, anterior tibial perforator, superficial circumflex iliac artery, deep inferior epigastric artery perforator, and supraclavicular and rectus abdominis musculoperitoneal flaps. Most of those flaps have shown good outcomes at the expense of a difficult dissection, donor site morbidity, inconvenience of flap harvest, or the need of more extensive (and expensive) preoperative evaluation, therefore, they are reserved as the second choice for comorbid patients or those in which traditional ALT or radial forearm could not be used for other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study confirms that a one-stage circumferential ABS release with the circular incision is considered a safe operation for the treatment of both circumferential and semi-circumferential ABS. Some authors reported the pelvic constriction band in a newborn female with ABS [11] …”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the pelvic constriction band in a newborn female with ABS. [11] In the treatment of constriction rings, the key to success is the complete resection of all constricting rings and the longitudinal incisions of the deep fascia. Scars should not cross joints longitudinally in order to prevent movement restrictions lead to scar contracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with our finding. The short and small caliber pedicle does not limit cases of tongue reconstruction [1,9,23].…”
Section: Discussionmentioning
confidence: 99%